A new method for flow cytometry-based detection of ABO antigen expression levels - ZHANG Yuyu; LIU Xi; XIE Junhua; CAO Bin; ZHENG Jiewei; ZHU Xinyi; WANG Zhongying; XIANG Dong (Zhongguo shuxue zazhi)
[Objective] To design and establish a new method for flow cytometry-based detection of commonly observed highly expressed antigens on red blood cells, and to further evaluate the differences and distribution characteristics of antigen expression levels between ABO blood type homozygotes and heterozygotes in healthy individuals. [Methods] Residual blood samples after donor blood type identification by Shanghai Blood Center in April 2024 were collected. Among them, samples of 19 homozygous and 19 heterozygous individuals of type A and type B were selected. Then the expression level of ABO antigen on red blood cells were detected using the new method established in this study and the traditional aldehyde fixed red blood cell method. Both methods were tested independently three times and the results were compared. [Results] The mean values of the three detection results of the new method was (×105/RBC): AA homozygous 3.3±0.5, AO heterozygous 2.8±0.3, BB homozygous 3.6±0.3, BO heterozygous 3.1±2.8. The mean values of the three detection results of the aldehyde fixation method were AA homozygous 5.9±0.9, AO heterozygous 5.0±1.4, BB homozygous 3.8±0.6, and BO heterozygous 3.3±0.4. The average antigen distribution of each genotype followed a normal distribution. Comparing the average antigen expression levels of homozygotes and heterozygotes, both methods showed that A/B homozygotes had higher antigen levels than heterozygotes, with AA being 1.17 to 1.18 times that of AO and BB being 1.15 to 1.16 times that of BO. Comparing the inter batch differences in the three test results of two methods, the new method showed no significant difference in the three test results for four genotypes (P>0.05). The aldehyde fixation method showed significant differences in the test results for all three genotypes (P<0.01) except for BB homozygotes (P>0.05). The reliability and reproducibility of the new method were better than those of the traditional aldehyde fixation method. [Conclusion] The antigen expression level of ABO homozygotes is higher than that of heterozygotes, and the difference in antigen level between type A homozygotes and heterozygotes is slightly higher than that of type B. The new method is superior to traditional aldolization fixation methods.